When Do Ineffective Audit Committee Members Experience Turnover? - Kachelmeier, Steven J.; Rasmussen, Stephanie J.; Schmidt, Jaime J. (Contemporary Accounting Research, 2016)
Abstract We use information extracted from a major proxy advisory service to test predictions from institutional theory regarding when and why audit committee ( AC ) members experience turnover because of evidence of ineffective governance. First, we broadly categorize AC ineffectiveness concerns as either (i) financial reporting failures or (ii) characteristics of individual AC members. Institutional theory suggests that the visible nature of the first category is more likely to threaten perceptions of AC legitimacy and hence prompt turnover, which is what we find. We then enrich the analysis by interacting the AC ‐member ineffectiveness indicators with the extent of shareholder protest votes, finding that shareholder dissent elevates the turnover effects of both categories of ineffectiveness, as institutional theory would predict. Finally, we find that otherwise effective AC members face an increased likelihood of turnover if they serve on the AC when financial reporting failures are discovered, even if they were not on the AC when the events precipitating the failures occurred. Overall, our findings support the institutional theoretic premise that boards take remedial actions when necessary to restore perceived legitimacy.